2020
DOI: 10.48550/arxiv.2003.02276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observable Gravitational Waves in Minimal Scotogenic Model

Debasish Borah,
Arnab Dasgupta,
Kohei Fujikura
et al.

Abstract: We scrutinise the widely studied minimal scotogenic model of dark matter and radiative neutrino mass from the requirement of a strong first order electroweak phase transition (EWPT) and observable gravitational waves at future planned space based experiments. The scalar DM scenario is similar to inert scalar doublet extension of standard model where a strong first order EWPT favours the low mass regime of DM, a narrow fine tuned region currently allowed from collider and direct detection bounds. In the fermion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…• Ω 1 h 2 conversion in scotogenic models can be sizeable and saturate experimental upper bounds on corresponding branching ratios for fermion DM scenario [65,137,138], in our model they are likely to be suppressed as the singlet fermions N 1,2 are heavier than the scale of leptogenesis.…”
Section: Dark Mattermentioning
confidence: 50%
See 1 more Smart Citation
“…• Ω 1 h 2 conversion in scotogenic models can be sizeable and saturate experimental upper bounds on corresponding branching ratios for fermion DM scenario [65,137,138], in our model they are likely to be suppressed as the singlet fermions N 1,2 are heavier than the scale of leptogenesis.…”
Section: Dark Mattermentioning
confidence: 50%
“…Another interesting prospect of probing our model can be in the form of gravitational waves from a strongly first order phase transition (SFOPT). In a recent work [138], it was shown that in the minimal scotogenic model, the criteria of SFOPT constrains the scalar sector a lot, leading to a scalar DM parameter space in tension with direct detection bounds. Due to the presence of an additional singlet scalar in our model whose mass is not as constrained as the inert doublet components, the SFOPT criteria is likely to be satisfied with more freedom.…”
Section: Dark Mattermentioning
confidence: 99%
“…As discussed in subsection II B, for a particular benchmark of SIDM parameter space, one requires a certain freeze-out abundance of N 1 so that correct SIDM relic abundance is generated at the end from non-thermal decay of N 1 . Therefore, we estimate the thermal freeze-out abundance of N 1 in the scotogenic model in a way similar to fermion DM studies in scotogenic model [81][82][83].…”
Section: Lightest Rhn Abundancementioning
confidence: 99%